Chromatic dispersion monitoring for next generation optical networks - Liu, Ning (2008)
Chromatic dispersion (CD) is one of the major factors limiting optical transmission distance. Therefore, it is essential to monitor the residual CD of individual wavelength channels so as to ensure that the residual CD does not exceed the designed tolerance. This thesis documents the investigations of cost-effective and high performance CD monitoring techniques.